Role of Hydrology in Managing Consequences of a Changing Global Environment 2010
DOI: 10.7558/bhs.2010.ic33
|View full text |Cite
|
Sign up to set email alerts
|

Rural land management impacts on catchment scale flood risk

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source• a link is made to the metadata record in Durham E-Theses• the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 299 publications
(494 reference statements)
0
2
0
Order By: Relevance
“…This study supports the findings of SEPA (2015), which revealed that traditional coping mechanisms include expanding burrow pits and dredging rivers to remove fine sand, clay, and small pieces of rock from the riverbed, which may boost the river's ability to carry water. clearing of obstructed drainages to enable water channelization (Pattison, 2021). This is especially crucial in view of predicted climate change, which indicates that the protective standards we put in place now may not be adequate in the coming decades.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study supports the findings of SEPA (2015), which revealed that traditional coping mechanisms include expanding burrow pits and dredging rivers to remove fine sand, clay, and small pieces of rock from the riverbed, which may boost the river's ability to carry water. clearing of obstructed drainages to enable water channelization (Pattison, 2021). This is especially crucial in view of predicted climate change, which indicates that the protective standards we put in place now may not be adequate in the coming decades.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This is especially crucial in view of predicted climate change, which indicates that the protective standards we put in place now may not be adequate in the coming decades. Planting cover-producing vegetation, such as grass or clover, as opposed to leaving bare soil, prevents soil erosion, preserves soil fertility, and lowers surface runoff (Pattison, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%